CHARACTERISTIC OF PATIENTS WITH REFRACTIVE DISORDER AT EYE CLINIC OF SANGLAH GENERAL HOSPITAL DENPASAR, BALI-INDONESIA - Handayani-Ariestanti, T.; Supradnya-Anom, I G.N; Pemayun-Dewayani, C.I. (BALI MEDICAL JOURNAL; Volume 1, Number 3, September-December 2012)
Objective: Refractive disorders are one of the most common causes of visual impairment worldwide and become the second leading cause of blindness that can be cured. This study aims to know the characteristic of refractive errors patients in Sanglah General Hospital in the period of 1 st January until 31 st December 2011. Method : This is a retrospective analytical descriptive study. Data were collected retrospectively from patient’s medical records with refractive errors and shown as frequency and percentage. Visual acuity before and after corrections were investigated and analyzed using McNemar Test. Results : from 579 patients, the most common diagnosis was astigmatism (40.1%), 63% were woman, 39.7% were older than 40 years old, and 60.2% live in Denpasar. In myopia cases, 69.7% patients were woman and 25.1% were between 11-20 years old. In astigmatism cases, 63.4% were woman, 57% were older than 40 years old. Of the hypermetropic cases, 61,3% were woman, 79.5% were older than 40 years. Among presbyopia cases, 53.2% patients were woman with 84.4% were older than 40 years. In McNemar test, there were a significant difference between visual acuity before and after correction in both eyes (p=0.0001). Most astigmatism was with the rule cases on both eyes. On the right eye 54.3% shows mild astigmatism, whereas on the left eye 50.8% shows moderate astigmatism. In hypermetropic cases 92.4% are mild degrees. While 55.5% presbyopic patients need additional glasses of +1.00 D up to +2.00 D. About 97.9% patients with refractive error were given glasses prescription. Conclusion: mostly refractive errors patient are woman and the most common diagnosis is astigmatism. There were significant differences of visual acuity before and after correction on both eyes (p=0.001).
Keywords: refractive error, visual acuity, eyeglasses